Diagnostic disclosure of Alzheimer's disease in Brazil: a national survey of specialized physicians - Souza, Vitor Santos de; Guazzelli, Sofia Brunchport; Cruz, Leonardo Cardoso; Resende, Elisa de Paula França; Souza, Leonardo Cruz de; Barbosa, Maira Tonidandel; Caramelli, Paulo (Arquivos de Neuro-Psiquiatria, 2023)
Background: The diagnosis of Alzheimer's disease (AD) can bring financial and emotional consequences to patients and caregivers. Whether or not the diagnosis should be disclosed to patients is a matter of debate amongst physicians and can be influenced by culture and experience.Objective: To investigate the current practice of physicians who attend and treat patients with dementia in Brazil regarding the disclosure of dementia diagnosis and compare the practice with what has been performed 15 years ago in the country.Methods: Data were evaluated using an electronic questionnaire. The questions used to carry out this research were similar to the questions of the study carried out 15 years ago 9. The form was sent to the Brazilian Academy of Neurology, the Brazilian Association of Geriatrics and Gerontology, and the Brazilian Association of Psychiatry, which forwarded it to their members. Analyses were conducted through non-parametric statistical tests, with a post-hoc assessment.Results: 397 physicians responded to the survey, of which 231 are neurologists, 124 geriatricians, 29 psychiatrists and 13 from other specialties. The mean age was 45.2 years. The majority (66.7%) of the physicians reveal the diagnosis of AD always or usually. The youngest group of neurologists were more likely to disclose the diagnosis than the oldest group with a significant difference between them. In comparison to the 2008 Brazilian study, the percentage of physicians who always or usually disclose the diagnosis has risen by 22%. On the other hand, 12.3% of the physicians rarely or never disclose the diagnosis, in comparison to 25,3% in 2008. The main reasons for not disclosing the diagnosis concern the patients' mental health.Conclusion: Advances in dementia knowledge and biomarkers availability probably explain the increase in the rate of disclosure. The main challenge is to reconcile the autonomy of affected individuals, mental health issues after the diagnosis and the family member's opinion.
Keywords: Alzheimer Disease; Diagnosis; Disclosure